SIMULASI DAN PEMBELAJARAN PASAL UNDANG-UNDANG PELANGGARAN LALU LINTAS DENGAN METODE COMPUTER BASED INSTRUCTION (CBI) PADA SISWA SMK PARULIAN MEDAN - Riswan Limbong; Pandi Barita Nauli Simangunsong (PUBLIKASI ILMIAH TEKNOLOGI INFORMASI NEUMANN (PITIN), 2019)
The law is a rule that must be applied in Indonesia in this case the law that is most often violated by the general public is the law on traffic violations, most traffic users often ignore this, due to a lack of understanding of the violation of the article on Constitution Computer Based Instruction is a method that makes computers as the main means or tools that communicate material to students. The computer learning model (CBI) aims to help students understand the lessons about law because this method includes Tutorial, Drill and Practice, Simulation and Games The results of the application are designed to be able to help millennials in learning and understanding about orderly and able comply with laws, especially millennials, to become role models in complying with traffic laws